F.A.Q. about mastering - Aydöner, Erman (Ankara: Müzik Eğitimi Yayınları, 2021)
Mastering is the last step in the music making process. Often times, this step is the least know. Some refer it as the dark art! "FAQ About Mastering" will help you to learn more about this art while showing you different perspectives of respected artist, mixers, and mastering engineers. With this book you will; - Find out what artists and mixing engineers expect from mastering, - Learn different ideas and approaches of top mastering engineers, - Find answers to your questions about mastering from great names such as Elliot Scheiner, Joe Barresi, Mike Fraser, Darcy Propher, Jonathan Wyner, Scott Hull, Tony Cousins, and many more...In addition, Erman Aydöner, who has worked as a mastering engineer for many years, shares some of his knowledge, experience and tips with you in this book.
1
Keywords: Müzik; Music